2001
DOI: 10.1046/j.1365-2672.2000.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biocontrol strains of Trichoderma on plant growth, Pythium ultimum populations, soil microbial communities and soil enzyme activities

Abstract: Five strains of Trichoderma with known biocontrol activities were assessed for their effect upon pea growth and their antagonistic activity against large Pythium ultimum inocula. The effect of Trichoderma inocula upon the indigenous soil microflora and soil enzyme activities in the presence and absence of Pythium is assessed. In the absence of Pythium, Trichoderma strain N47 significantly increased the wet shoot weight by 15% but did not significantly affect the dry weight, whilst strains T4 and N47 significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
86
1
11

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(107 citation statements)
references
References 27 publications
9
86
1
11
Order By: Relevance
“…Another benefit that could be given to plants, such as IAA hormone produced by Trichoderma to spur the development of plant roots (Harman, 2000). This was in line with research done by Naseby et al (2000), which showed that Trichoderma could increase root weight and dry weight of bean plants, compared with no Trichodema.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another benefit that could be given to plants, such as IAA hormone produced by Trichoderma to spur the development of plant roots (Harman, 2000). This was in line with research done by Naseby et al (2000), which showed that Trichoderma could increase root weight and dry weight of bean plants, compared with no Trichodema.…”
Section: Discussionsupporting
confidence: 92%
“…Remarks: The numbers in the columns and / or rows followed by the same letter were not significantly different according to Duncan Multiple with α = 5%; (+): there was interaction between factors tested; Data was transformed with a log x. was done to facilitate the formation of seeds (Elias, 2006). Response of plant growth caused by Trichoderma depends on their ability to survive and thrive in root zone (Naseby et al, 2000). It could give a great influence on roots formation and yield (Harris et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…have beneficial effects on plants. For instance, there are commercial agricultural products containing T. atroviride, T. harzianum and T. hamatum (Ha, 2010) that promote plant growth (Chang et al ., 1986; Gravel et al ., 2007; Contreras‐Cornejo et al ., 2009), reduce the severity of plant diseases (Naseby et al ., 2000; Nawrocka and Malolepsza, 2013) and enhance tolerance to abiotic stresses (Bae et al ., 2009; Montero‐Barrientos et al ., 2010; Dixit et al ., 2011; Contreras‐Cornejo et al ., 2014). In addition, Trichoderma sp.…”
Section: Discussionmentioning
confidence: 99%
“…em manchas-foliares, pode-se citar o controle de Pythium sp. (NASEBY et al, 2000) e de Cilindrocladium spathulatum em erva-mate (GOMES et al, 2001 Um disco de 5 mm de diâmetro da cultura pura do patógeno foi retirado do centro da placa e transferido para uma placa contendo apenas BDA. Após 48 h, um disco do isolado de Trichoderma spp.…”
Section: Introductionunclassified